Novel Insights into Neuroprotective Strategies Employing NQO1 and DCLK1 in Parkinson’s Disease - Kandage, M. Shyami; Silva, N. Gayathri; Gamage, K. Kanchana (My University, 2021)
Parkinson’s disease (PD) is the most common movement disorder and is only second to Alzheimer’s disease in most prevalent neurodegenerative diseases. Diverse causative factors lead to PD pathology among which oxidative stress and accumulation of α-Synuclein aggregates are considered to be key determinants for both sporadic and familial forms. In this review we focus on two novel research efforts to block elevated oxidative stress and α-Syn aggregates to provide neuroprotection to the dopaminergic neurons and thereby alleviating the motor symptoms displayed in PD animal models. A recently published effort from Luo and colleagues, discovered a pathway where the neuroprotective protein NQO1 is degraded upon phosphorylation by activated Akt and making the dopaminergic neurons susceptible to demise via elevated oxidative stress. Another recent report by Vázquez-Vélez and colleagues explored the regulatory relationship between the neuron expressed kinase DCLK1 and α-Syn in the context of human cellular and mouse models. These discoveries concentrate on different mechanisms of preventing the dopaminergic neurodegeneration in PD by reducing the oxidative stress and α-Syn aggregation via regulating key determinants of PD pathophysiology, NQO1 and DCLK1 respectively. This review emphasizes the possibility of employing both NQO1 and DCLK1 as promising therapeutic targets leading to future prospects of combinational therapies for devastating diseases like PD.
Keywords: Parkinson’s disease; neurodegeneration; α-synuclein; dopaminergic neurons